Practical interventions for young people at risk - Geldard, Kathryn (Los Angeles : Sage, 2009)
'The book's rich, relevant and comprehensive contributions from experienced writers make it a substantial resource for teaching, reference and research' - Mark Prever, trainer, writer and supervisor. 'The needs and problems of young people are currently extremely topical and justify a dedicated textbook. The wide range of internationally renowned authors contributes to the strengths and diversity of this publication, enhancing its potential as a resource for students and professionals' - Jenny Pinfield, University of Worcester. This book responds to the urgent need for practical intervention approaches targeting young people at risk. It provides a much needed practical resource for practitioners and students from a variety of helping professions. Focussing on interventions that practitioners can use in collaboration with the young person, the book offers hands-on strategies for addressing challenges and issues typically faced by young people, such as: depression, suicide and self-harm; substance misuse; problematic sexual behaviour; marginalised youth; and, mental health issues. Throughout the book, multi-disciplinary and international authors share their expertise, highlighting relevant evidence-based interventions and considering themes such as anti-oppressive practice, culture, values and ethics. It will prove invaluable reading for students and practitioners working with young people, especially in the fields of youth work, social work, psychology, counselling, and education.
Pt. 1. Introduction -- Engaging young people collaboratively / Kathryn Geldard -- pt. 2. Building on strengths -- Promoting self-care behaviours / David Geldard -- Building resilience to prevent mental health problems in young people: the resourceful adolescent programme (RAP) / Ian Shochet, Rebecca Hoge and Astrid Wurfl -- Enhancing peer support / Kathryn Geldard and Wendy Patton -- pt. 3. Suicide and self-harm -- Combating depression / Alan Carr -- Empowering young people who self-harm / Jude Sellen -- Preventing suicide / Alan Carr -- pt. 4. Confrontational behaviour -- Working with gangs and other delinquent groups / Simon Hallsworth and Tara Young -- Prevention and responses to bullying / Fran Thompson, Neil Tippett and Peter K. Smith -- Intervening with youth who engage in fire-setting / Daryl L. Sharp, Robert E. Cole, Carolyn E. Kourofsky and Susan W. Blaakman -- pt. 5. Substance abuse -- Alcohol and young people / Brad Levingston and Jenny Melrose -- Tackling the misuse of volatile substances / Richard Ives -- Responding to the use of illicit drugs / Cindy M. Schaeffer, Rocio Chang and Scott W. Henggeler -- pt. 6. Sexual behaviour -- Sexual health-related interventions / Susan Moore -- Young people with sexual behaviour problems: towards positive and healthy relationships / Ian Lambie -- pt. 7. Mental health -- Addressing eating problems / Renee Rienecke Hoste and Daniel le Grange -- Responding to cult group membership / Lee Richmond and Carole Rayburn -- pt. 8 Marginalised young people --Understanding young people in care / Jan Foster.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social work with youth; Youth -- Services for; Needs assessment; Crisis intervention (Mental health services); Electronic books